Bosnia, Bosnia! - Németh, Péter Gábor (Wizner, Balázs, 2012)
Verzio9 FF Submission. Duration: 01:00:00 In 1992, patients from a local psychiatric institute in Bosnia were rescued from the war and brought to Hungary, where they stayed in a makeshift secure psychiatric unit in the country’s biggest refugee camp. Since then they’ve been waiting impatiently to return home. For seventeen years their case seems to be stuck in the labyrinth of politics and bureaucracy. Finally, long after the end of hostilities, the two countries arrange for their return. Some of the asylum residents did not live long enough to see that day. Others are so weak that they risk their lives just making the journey. What kind of future awaits them in their homeland? The makers of the film follow the tragic and heartbreaking story of the last victims of a war that lasted from 2003 to 2011.